Financial Literacy and Its Determinants: A Case of Professionals in Colombo District Sri Lanka - Madhushani, P.W.G.; Rajapakse, R.P.C.R. (University of Jaffna, 2023)
This observation intends to examine the financial literacy level of professionals working in the professions of Medicine (Doctors), Engineering (Engineers), Management (Managers), Law (Lawyers) inclusive Aviation and Navigation (Captains and Pilots), and its determinants. The methodology was a quantitative survey approach involving a sample of 300 respondents from the Colombo district. The analysis revealed that Basic and Advanced financial literacy among professionals is at a medium level. However, the level of financial literacy was not at a satisfactory level among non-management professionals, particularly doctors and lawyers. The results of the Regression analysis revealed that Economic and financial education, self-analytical skills, the field of employment, and monthly income level as influential determinants of financial literacy. The professions with less exposure to economic and financial education have low financial literacy. Findings demonstrate the growing importance of implementing a national strategy to improve financial and economic educational programmes, particularly for individuals who are not working in the professions related to management.
Keywords: Basic financial literacy; Financial; Economic education; Self-analytical skills; JEL classification: F36, I22